Recruitment and Retention of New Emergency Medical Technician (EMT)-Basics and Paramedics. (8th December 2016) - Chapman, Susan A.; Crowe, Remle P.; Bentley, Melissa A.
Abstract: Objectives: The purpose of this paper is to describe factors important for the recruitment and retention of Emergency Medical Technician (EMT)-Basics and EMT-Paramedics new to the Emergency Medical Services (EMS) field (defined as two years or less of EMS employment) through an analysis of 10 years of Longitudinal EMT Attributes and Demographic Study (LEADS) data. Methods: Data were obtained from 10 years of LEADS surveys (1999-2008). Individuals new to the profession were identified through responses to a survey item. Their responses were analyzed using weights reflecting each individual's probability of selection. Means, proportions, and 95% confidence intervals (CIs) were determined and used to identify statistically significant differences. Results: There were few changes in the demographic characteristics of new EMT-Basics and Paramedics across survey years. New EMT-Basics tended to be older and less likely to have a college degree than new EMT-Paramedics. More new EMT-Basics than EMT-Paramedics worked in rural areas and small towns and reported that they were working as a volunteer. There were differences between new EMT-Basics and EMT-Paramedics in several of the reasons for entering the profession and in facets of job satisfaction. Conclusions: The findings provide guidance for recruiters, educators, employers, and governmental EMS policy organizations and will provide better insight into how to attract and retain new entrants to the field. SA Chapman, RP Crowe, MA Bentley .Recruitment and retention of new Emergency Medical Technician (EMT)-Basics and Paramedics .Prehosp Disaster Med .2016 ;31 (Suppl.1 ):s70 –s86 .